Aplicação de programação linear na seleção de carteiras de investimento - Siervo, Juliano Squarsone Di (Universidade Federal de São Carlos, 2017)
It is shown in this dissertation the applicability of Harry M. Markowitz´s Modern Theory, allied to Operation Research, in the diversification of actions in an investment portfolio, minimizing its total risk in a given expected feedback. So, Linear Programming is used in order to model the portfolio´s variance, and the Simplex Method to determine the optimized portfolio. In a second step, Quadract Programming is used in order to model the portfolio´s variance and the model is implemented in the software MATLAB. Based on the results, their relevance an advantages are discussed.
Application of linear programming in the selection of investment portfolios
Keywords: Programação Linear; Método Simplex; Teoria Moderna de Portfolio de Markowitz; Linear Programming; Simplex Method; Harry M. Markowitz´s Modern Theory; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA